2009
DOI: 10.1103/physrevd.80.065030
|View full text |Cite
|
Sign up to set email alerts
|

’t Hooft-Polyakov monopoles in latticeSU(N)+adjoint Higgstheory

Abstract: We investigate twisted C-periodic boundary conditions in SU(N ) gauge field theory with an adjoint Higgs field. We show that with a suitable twist for even N one can impose a non-zero magnetic charge relative to residual U(1) gauge groups in the broken phase, thereby creating a 't Hooft-Polyakov magnetic monopole. This makes it possible to use lattice Monte-Carlo simulations to study the properties of these monopoles in the quantum theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…While, at In compositions of 43 % or higher, peaks related to the cubic structure of (In x Ga 1x ) 2 O 3 were apparent, indicating the phase separation. Consequently, it was concluded that the solubility limit was between 35% and 43%, and this value of approximately 40% is similar to those in other reports of powder synthesis [12][13][14][15]. Figure 4 shows the transmission spectra of these films.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…While, at In compositions of 43 % or higher, peaks related to the cubic structure of (In x Ga 1x ) 2 O 3 were apparent, indicating the phase separation. Consequently, it was concluded that the solubility limit was between 35% and 43%, and this value of approximately 40% is similar to those in other reports of powder synthesis [12][13][14][15]. Figure 4 shows the transmission spectra of these films.…”
Section: Introductionsupporting
confidence: 84%
“…However, β-Ga 2 O 3 and In 2 O 3 belong to different crystal systems, that is, a monoclinic system [10] and a cubic system [11], respectively, and this leads to the phase separation. According to the reports on (In x Ga 1-x ) 2 O 3 powder synthesis, where x represents the In composition, the solubility limit of In 2 O 3 into Ga 2 O 3 without phase separation was found to be about 40% [12][13][14][15]. In contrast, there have been few attempts to grow (In x Ga 1-x ) 2 O 3 thin films [16], and no indication was given on the solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…Though the algorithm works well for the one-dimensional lattice, for the 3 × 3 lattice, it is beyond the capabilities of a standard desktop machine. However, the method can be useful in finding a parametrization of the SU(N) matrices [38] and hence can then be used, for example, to extend the method of restricting a path integral of the SU(N) Georgi-Glashow model to the 't Hooft-Polyakov sectors by using the twisted C-periodic boundary conditions [4] for odd N and to precisely define the modified lattice Landau gauge for the SU(3) case.…”
Section: Discussionmentioning
confidence: 99%
“…We can derive link variables u corresponding to this smaller gauge group [20,21] u ¼ Å þ ðxÞU ðxÞÅ þ ðx þÞ;…”
Section: Lattice Implementationmentioning
confidence: 99%